Metabolite profile in hereditary spastic paraplegia analyzed using magnetic resonance spectroscopy: a cross-sectional analysis in a longitudinal study - Montanaro, Domenico; Vavla, Marinela; Frijia, Francesca; Coi, Alessio; Baratto, Alessandra; Pasquariello, Rosa; Stefan, Cristina; Martinuzzi, Andrea (Frontiers in Neuroscience, 2024)
Background: Hereditary Spastic Paraplegias is a genetic neurodegenerative disorder affecting the corticospinal tract. No established neuroimaging biomarker is associated with this condition. Methods: 46 patients affected by HSP and 46 healthy controls (HC) matched by age and gender underwent a single-voxel spectroscopy sampling (MRS) of bilateral pre-central and pre-frontal regions. MRS data were analyzed cross-sectionally (at T0 and at T1) and longitudinally (T0 vs T1). Results: At T0 mI/Cr in the pre-central areas of HSP was higher than HC. In the left (L) pre-central area NAA/Cr was significantly lower in HSP than in HC. In the right (R) pre-frontal area NAA/Cr was significantly lower in HSP than in HC. HSP SPG4 subjects showed significantly lower Cho/Cr concentration in the L pre-centralin L pre-central area than HC. Comparing SPG4 vs non-SPG4 among HSP subjects, in the L pre-central area mI/Cr in non-SPG4 were significantly higher than SPG4 subjects. In the R pre-frontal area, NAA/Cr was reduced and ml/Cr higher in non-SPG4 with respectnon-SPG4 respect SPG4 patients. Comparing “pure” and “complex” forms between them, NAA/Cr was higher in pHSP than in cHSP in the R pre-central area and in the R pre-frontal area. The longitudinal analysis involved fewer patients (n=30) and showed an increase of mI/Cr concentration in the L pre-frontal area among HSP subjects with respectsubjects respect to baseline. The patients had a significantly higher SPRS score at follow-up, with significant positive correlation with mI/Cr in the L pre-central area, while in bilateral pre-frontal areas at lower values of SPRS corresponded to highercorresponded higher NAA/Cr concentrations. To explore the discriminating power of MRS in identifying correctly HSP and controls, with an inference tree methodology it was possible to classify HSP subjects and controls with an overall accuracy of 73.9%, a sensitivity of 87.0% and a specificity of 60.9%. Conclusion: This pilot study indicates that brain MRS is a valuable approach, potentially exploitable as an objective biomarker in HSP.